O SAEB EM DEBATE: AVANÇOS E DESAFIOS DA POLÍTICA NACIONAL DE AVALIAÇÃO DA EDUCAÇÃO BÁSICA - Andrade, Talita Emidio (2022)
This research was developed with the objective of analyzing the historical trajectory of Saeb to the over thirty years of implementation, identifying the principles and concepts that underlie the system. For this, it assumes as guiding question: in which